The Pharmacological Importance of Nigellasativaas Radioprotective Agent - Martini, A. A. Kompiang; Sukrama, I Dewa Made (International Journal of Innovative Research in Medical Science, 2019)
Background: Many studies have showed that Nigella sativa is used as a natural remedy in treating various diseases across the globe. Indonesia is famous for its rich spices, one of which is the "Black Cumin" seed extract (Nigella Sativa N.S). Purpose: To analyze the effects of Nigella sativa as an antioxidant to inhibit oxidative stress caused by ionizing-free radiation. Result: Nigella sativa is widely used to diagnose, treat disease, and decrease the level of malondialdehyde (MDA) as one of the final markers of oxidative stress. Nigella sativa has been used as a treatment for various types of diseases in the world. Through the components contained in Nigella sativa it is believed to have uses as an antimicrobial, anti-inflammatory, antibacterial, antiviral, and as an antioxidant. Th[e mechanism of action of Nigella sativa depends on the type of disease. The contents of Nigella sativa are essential oils and thymoquionoe, dithymoquinone, thymol, carvacrol, nigellicine, nigellidine, nigellimine-N-oxide and alpha-hedrine. As well as some vitamins and omega 3 contained in it. The content of Nigella sativa will work together by inhibiting the okidasin reaction. Conclusion: Nigella Sativa can be used in herbal medicine because it has pharmacological effects; antibacterial, antifungal, antiviral and antioxidant. Nigella sativa has many health benefits. Nigella sativa contains thymoquinone which can reduce lipid peroxidation and increase antioxidant enzymes. The effectiveness of Nigella sativa as a radioprotector can prevent the occurrence of free radicals caused by ionizing radiation.